2018
DOI: 10.1016/j.ijrobp.2017.08.033
|View full text |Cite
|
Sign up to set email alerts
|

Identification of ATIC as a Novel Target for Chemoradiosensitization

Abstract: These findings implicate ATIC as an effective, and previously unrecognized, target for chemoradiosensitization and, more broadly, suggest that purine levels in cells might have an underappreciated role in modulating the efficiency of DNA damage responses that could be exploited in radiosensitizing strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 44 publications
0
24
0
Order By: Relevance
“…Moreover, a study found by exome sequencing conducted on radiosensitive cell line derived from patients suspected of having ataxia‐telangiectasia and Lesch‐Nyhan spectrum disorders, a heterozygous complex frameshift mutation c.[130dup;131_132insA] in the ATIC gene, of unknown significance 15 . This variation is also carried by eight heterozygous Europeans in gnomAD, while neither c.130dup nor c.131_132insA alone is reported.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a study found by exome sequencing conducted on radiosensitive cell line derived from patients suspected of having ataxia‐telangiectasia and Lesch‐Nyhan spectrum disorders, a heterozygous complex frameshift mutation c.[130dup;131_132insA] in the ATIC gene, of unknown significance 15 . This variation is also carried by eight heterozygous Europeans in gnomAD, while neither c.130dup nor c.131_132insA alone is reported.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that ATIC is a bifunctional protease that catalyzes the last two steps in the purine biosynthesis pathway. Depletion of ATIC or suppression of its transformylase activity significantly decreased the survival rate of cells in clonogenic survival assays, which indicates that ATIC may promote the proliferation and migration in cancer cell lines [33]. Indeed, suppression of ATIC expression significantly inhibited the ability of HCC cells to proliferate and migrate through the regulation of the AMPK-mTOR-S6K1 signaling pathway.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have reported that ATIC is a bifunctional protease that catalyzes the last two steps in the purine biosynthesis pathway. Depletion of ATIC or suppression of its transformylase activity significantly decreased the survival rate of cells in clonogenic survival assays, which indicates that ATIC may promote the proliferation and migration in cancer cell lines [32]. Indeed, suppression of ATIC expression significantly inhibited the ability of HCC cells to proliferate and migrate through the regulation of the AMPK-mTOR-S6K1 signaling pathway.…”
Section: Discussionmentioning
confidence: 94%